الأليات الإجرائية لمكافحة جريمة الإختلاس - دنيا نصري; حكيمة سيساوي (My University, 2021)
Abstract : In the context of combating the crime of embezzlement, the Algerian legislator relied on important procedural rules represented in preventive and judicial mechanisms. The first is the obligation of the public employee to declare his financial receivables, and this is what Article 02 of the Prevention and Combating of Corruption Law states as a precautionary and preventive measure, in addition to the necessity of establishing a national authority whose role is limited to suggesting recommendations and collecting information to enhance responsibility during the performance of its tasks. As for the judicial aspect, the Algerian legislator worked to create the Accountability Council in charge of post-monitoring oversight of state funds and public utilities, with its issuance to the central office specialized in research and application of deterrence, as well as its adoption of special methods of investigation such as surveillance and handing over the observer, not to mention his initiative to establish specialized judicial poles in order to keep pace with development The massive crime of embezzlement, which falls within the scope of the judicial organization. ................ ملخص اعتمد المشرع الجزائري في إطار مكافحة جريمة الاختلاس إلى قواعد إجرائية هامة المتمثلة في الآليات وقائية وأخرى قضائية. تتمثل الأولى في إلزامية الموظف العمومي التصريح بذممه المالية وهذا ما جاءت به المادة 02 من قانون الوقاية من الفساد ومكافحته باعتباره إجراء احترازي ووقائي بالإضافة إلى ضرورية إنشاء الهيئة الوطنية الذي يقتصر دورها على اقتراح توصيات وجمع المعلومات الكفيلة لتعزيز المسؤولية أثناء أداء مهامها. أما من الناحية القضائية التي عمل المشرع الجزائري على استحداث مجلس المحاسبة المكلف بالرقابة البعدية على أموال الدولة والمرافق العمومية، مع إصداره للديوان المركزي المختص بالبحث وتطبيق الردع، وكذا انتهاجه لأساليب خاصة بالتحري كالترصد وتسليم المراقب ناهيك عن مبادرته في إنشاء أقطاب قضائية متخصصة من اجل مسايرة التطور الهائل لجريمة الاختلاس والتي تدخل ضمن نطاق التنظيم القضائي. .................. Résumé Dans le cadre de la lutte contre le crime de détournement de fonds, la législation algérienne a adopté d’importantes règles de procédure: Mécanismes préventifs et judiciaires. Le premier est l’obligation d’un fonctionnaire de déclarer ses finances. L’article 02 de la Loi sur la prévention et le contrôle de la corruption le stipule à titre de mesure de précaution et de prévention, ainsi que la nécessité de créer un organisme national dont le rôle se limite à proposer des recommandations et à recueillir des informations pour renforcer la responsabilité dans l’exercice de ses fonctions. Le législateur algérien a créé le Conseil comptable pour le contrôle à distance des fonds de l’État et des services publics et l’a délivré à l’Office central de la recherche et de l’application de la dissuasion, ainsi que des méthodes d’enquête telles que la surveillance et la remise du contrôleur, sans oublier son initiative dans la mise en place de pôles judiciaires spécialisés afin de suivre le rythme du développement dramatique du crime de détournement dans le cadre de la réglementation judiciaire.